The development of xenograft glioblastoma implants in nude mice brain - Behar, FM (Carol Davila University Press, 2008)
The inefficacity of the actual therapies for glioblastoma multiformis stimulates the researchers to search for new and innovative therapies. Therefore, the development of in vivo model for glioblastoma is an essential step during these researches, being a link between cells cultures studies and the first phases of clinical trials. In this paper, we present several procedures which have been performed for the first time in our country, such as: the cultivation and manipulation of U87MG line, the manipulation of athymic – knock–out mice (NUDE Crl: CD–1 Foxn1), the stereotactic inoculation of glioblastoma cells and finally the development of glioblastoma xenograft in the brain of inoculated nude mice. These results, which offer to the researchers from our country an in vivo model for glioblastoma, could be the start point for several projects oriented to the development of new therapies in glioblastoma, and could raise the performance of our scientific research to the European level.